DEVELOPMENT OF A VOCATIONAL SKILLS TRAINING MODEL FOR CONSTRUCTION WORKERS - Lilis Widaningsih; Fauzi Rahmanullah; Trias Megayanti; Yudhistira Kusuma; Indah Susanti (Universitas Pendidikan Indonesia, 2023)
The development of culture and technology in responding to human needs in architecture and physical infrastructure development requires an acceleration in the skills of construction workers. Many factors become obstacles for construction workers to be able to compete and improve their skills. One of them is access to education and skills training because of the lack of information and opportunities they can get. This study aims to develop a vocational skills training model oriented to the certification of skilled workers in the construction industry. The development of the training model is made through stages that refer to research and development of Logic Model Development. The process carried out includes the planning, implementation, analysis, testing and finalization of the training model. Data collection was carried out through surveys of construction worker service users, FGD with training model development experts, FGD with construction industry stakeholders, theoretical analysis, and policies as materials for model development. The findings of this study are in the form of a training model that develops networks and collaborations between institutions related to skilled workers in the construction industry. Vocational universities have the potential to strengthen and facilitate construction workers in improving job skills and certifying skilled workers. In the long term, this model is expected to become a prototype for a sustainable vocational skills training system for construction workers.